The National Criticality Experiments Research Center and its role in support of advanced reactor design - Thompson, Nicholas W.; Maldonado, Alexis; Cutler, Theresa E.; Trellue, Holly R.; Amundson, Kelsey M.; Rao Dasari, Venkateswara; Goda, Joetta M.; Grove, Travis J.; Hayes, David K.; Hutchinson, Jesson D.; Kistle, Hadyn M.; Kostelac, Cole M.; et al. (Frontiers in Energy Research, 2023)
The National Criticality Experiments Research Center (NCERC) located at the Nevada National Security Site (NNSS) in the Device Assembly Facility (DAF) and operated by Los Alamos National Laboratory (LANL) is the only general purpose critical experiments facility in the United States. Experiments from subcritical to critical and above prompt critical are carried out at NCERC on a regular basis. In recent years, NCERC has become more involved in experiments related to nuclear energy, including the Kilopower/KRUSTY demonstration and the recent Hypatia experiment. Multiple nuclear energy related projects are currently ongoing at NCERC. This paper discusses NCERC’s role in advanced reactor design and how that role may change in the future.